THE USING OF GAME TECHNOLOGIES IN PRIMARY EDUCATION WAYS TO DETERMINE THE INTERESTS OF STUDENTS - Jumayeva Gulnora Tursunpulatovna; Turgunova Sabokhat Shadiyevna (American Journals, 2023)
This article deals with game technologies in primary education and the use and benefits of using this technology are discussed. In addition, there are examples of effective games that can be used in the course of the lesson.
Keywords: Primary education, game, child, subject, role, didactics, creative activity, achievement, active, method.